2020
DOI: 10.1016/j.clinbiochem.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-related peptidases protein expression in lymphoid tissues suggests potential implications in immune response

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These are singledomain serine proteases secreted as inactive zymogens (pro-KLKs). Under normal physiological conditions, KLKs are expressed in a variety of tissues with certain members displaying tissue-restricted patterns, whereas others having broad tissue expression patterns [136][137][138]. Reflecting their broad spectrum of tissue expression, KLKs are involved in a variety of biological processes and have been associated with several diseases such as cancer, inflammation and neurodegeneration [139].…”
Section: Inhibition Of Kallikrein-related Peptidase Activity 2211 Tissue Kallikrein Expression and Physiological Functionmentioning
confidence: 99%
“…These are singledomain serine proteases secreted as inactive zymogens (pro-KLKs). Under normal physiological conditions, KLKs are expressed in a variety of tissues with certain members displaying tissue-restricted patterns, whereas others having broad tissue expression patterns [136][137][138]. Reflecting their broad spectrum of tissue expression, KLKs are involved in a variety of biological processes and have been associated with several diseases such as cancer, inflammation and neurodegeneration [139].…”
Section: Inhibition Of Kallikrein-related Peptidase Activity 2211 Tissue Kallikrein Expression and Physiological Functionmentioning
confidence: 99%
“…Kallikrein-related peptidases (KLKs) have been reported to possess novel functions in innate immunity and inflammation. KLK10 is expressed in the follicular dendritic cells that are essential for the maturation of B cells (40). KLK10 was dynamically regulated in T cells in vitro in response to viral antigens and in activated monocytes, pointing to its activities in the development of adaptive and innate immune function (41).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, it was shown that KLK6 is highly expressed in primary melanoma, which points to its involvement in the neoplastic processes and malignant progression 57 . As for KLK10 , it is expressed in the follicular dendritic cells that are essential for the maturation of B cells which suggest possible implications in the regulation of immune cells in lymphoid tissues 70 . As for the KLK10 gene, we found an overexpression in XP patients.…”
Section: Discussionmentioning
confidence: 99%